PENGARUH PENGERASAN MATA GERGAJI DAN POLA PENGGERGAJIAN TERBADAP. KARAKTERISTIK PENGGERGAJIAN KAYU SENGON (Paraserianthes falcataria) - Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper deals with the study of charaetmstlc and sawing recovery of sengon (Peraserianthes falcataria). The materials used in this study consiat of 12c logs with 200 cm long and diameter ranging from 35,5 -36,5 cm. Three types. of sawtooth edge profile. were prepared to saw the logs, i.e. full stellite tipped, alternate-one stellits tipped and alternate –twostellitetipped. the power consumption and feed aped produced by each type of sawtooth were observed and analysed. in the study of sawn timber production two sawing patterns were applied.the parameters investigsted compriss recovery, productivity, board composition and visual defect,results of the study revsal that saw blade with alternate two steliite tipped consumes the lowest power and its feeding speed is the highest. in addition the semi quarter sawing yields recouery 4.5 % higher than live sawing pattern.meanwhile.the sawing productivity between two sawing patterns is not significantly different. the live sawing pattern produces 61 % boards of 15 and 17,5 cm wide; whereas semi quarter sawing produces 42% boards of 10 and 12,5cm. wide. the main defects of boards are knots,splits and shakes.